Registration of 'WA‐LE1', an edible oil camelina cultivar. Issue 2 (23rd April 2022) - Craine, Wilson; Lu, Chaofu; Garrison Garneau, Matthew; Bates, Philip; Hulbert, Scot
Abstract: Erucic acid concentration in oil of most camelina ( Camelina sativa L. Crantz) genotypes exceeds the 2% threshold allowed by the U.S. Food and Drug Administration (FDA) for use as a food additive. Lowering erucic acid concentration below the FDA threshold enables marketing camelina as edible oil for human consumption, greatly expanding potential uses to include food ingredients such as marinades, salad dressings, spreads, and dips. A mutant camelina line, LE1914, created via ethyl methanesulfonate mutagenesis at one FAE1 locus ( FAE1‐B ), produces seed oil with low (∼0.6%) erucic acid concentration (LE). This mutant trait was introgressed into elite camelina breeding lines to create LE lines adapted to Pacific Northwest dryland agriculture. These LE lines were evaluated in a large, replicated field trial in Pullman, WA, in 2019. One line, 'WA‐LE1' (Reg. no. CV‐15, PI 699653), exhibited agronomic performance similar to check cultivars while maintaining the low (∼0.6%) erucic acid concentration necessary for FDA approval as a food additive. WA‐LE1 is an edible oil camelina cultivar that also contains the Group 2 herbicide resistance trait of WA‐HT1 that was released in 2018. WA‐LE1 should expand marketability and increase profitability of camelina crops in the Pacific Northwest. Core Ideas: A mutation causing low erucic acid content was incorporated into a highly productive camelina cultivar, 'WA‐LE1'. The low erucic acid trait is required by the FDA for food use. A food market will expand the utility of camelina beyond biofuels. 'WA‐LE1' carries a gene for tolerance to Group 2 herbicides.